ARTICULAR SYNDROME IN THE PRACTICE OF A RHEUMATOLOGIST - N.Kh. Tukhtayeva., M.Sh. Karimov, K.E.Azadaeva (Galaxy International Interdisciplinary Research Journal, 2023)
Articular syndrome is a clinical set of symptoms, expressed by joint pain, morning stiffness, joint deformity, mobility restriction, and pathological changes in the ligaments. The most important diagnosis components for the disease underlying the patient’s existing articular syndrome are: a properly collected anamnesis, a medical examination, a complex of laboratory tests and radiation imaging methods.